ORANGE COUNTY - Timpone, Tara; Gardiner, Greg; White, Mike, 1970-; Rudin, Scott, 1958-; Kasdan, Jake, 1975-; Hanks, Colin, 1977-; Black, Jack, 1969-; O'Hara, Catherine; Fisk, Schuyler; Lithgow, John, 1945-; Tomlin, Lily (Widescreen DVD collection., 2002)
Inspired by acclaimed author Martin Skinner, Shaun Brumber realizes his life ambition and through a host of hilarious circumstances attempts to realize his dream.